Competency of triage nurse in the emergency department: A scoping review protocol - Miao Yu; Li Ma; Qingbian Ma (PLoS ONE, 2025)
Introduction Triage is an essential strategy to mitigate crowding and guarantee patients’ safety in emergency departments. To improve the quality of triage in emergency departments, Nurses should be equipped with the necessary competencies. Therefore, this review aims to synthesize available evidence on the competency elements required for triage nurses in emergency departments and to identify factors that influence their competency development. Methods and analysis This scoping review will be implemented following the five steps outlined by Arksey and O’Malley. We will use the PCC (population, concept, context) frameworks-Triage nurse (Population), Nursing competency (Concept), and EDs (Context)- to determine the research questions, and formulate the search terms. We will search six electronic databases including PubMed, Embase, CINAHL Plus, Web of Science, and two Chinese databases (China National Knowledge Infrastructure and Wangfang Data). Internet resources including WorldCat, and Google Books will be also searched to ensure comprehensive coverage. Studies will be selected by two independent authors based on defined eligibly criteria, and completed in August 2025. This will be followed by data extraction, and summarizing in October 2025. Then, evidence will be synthesized using descriptive statistics and thematic analysis. Five-domain Consolidated Framework for Implementation Research will be used to guide our thematic analysis of barriers and facilitators to development of competency. The results will be presented in December 2025. Findings from this scoping review will be beneficial to develop the training programs to facilitate the successful transition of nurses into effective triage nurse roles in the future. Registration The scoping review was registered in Open Science (https://osf.io/6fcr4).